Left Ventricular Outflow Tract Obstruction in Hypertrophic Cardiomyopathy Patients Without Severe Septal Hypertrophy. (July 2015) - Patel, Parag; Dhillon, Ashwat; Popovic, Zoran B.; Smedira, Nicholas G.; Rizzo, Jessica; Thamilarasan, Maran; Agler, Deborah; Lytle, Bruce W.; Lever, Harry M.; Desai, Milind Y.
<x xml:space="preserve">Abstract</x> Background— In patients with hypertrophic cardiomyopathy and left ventricular outflow tract (LVOT) obstruction, but without basal septal hypertrophy, we sought to identify mitral valve (MV) and papillary muscle (PM) abnormalities that predisposed to LVOT obstruction, using echo and cardiac magnetic resonance. Methods and Results— We studied 121 patients with hypertrophic cardiomyopathy hypertrophic cardiomyopathy (age, 49±17 years; 60% men; 57% on β-blockers) with a basal septal thickness of ⩽1.8 cm who underwent echocardiography (rest+stress) and cine cardiac magnetic resonance. Echo measurements included maximal LVOT gradient (rest/provocable), MV leaflet length (parasternal long, 4 and 3-chamber views), and abnormal chordal attachment to mid/base of anterior MV. Cine cardiac magnetic resonance measurements included basal septal thickness, number/area of PM heads, and bifid PM mobility (in systole and diastole). Mean basal septal thickness, LVOT gradient, and LV ejection fraction were 1.5±0.3 cm, 72±54 mm Hg, and 61±6%, respectively. The number of anterolateral and posteromedial PM heads was 2.7±0.7 and 2.6±0.7, respectively. Anterolateral and posteromedial PM areas were 19.9±7 cm2 and 17.1±6 cm2, respectively. PM mobility was 11±6°. On multivariable analysis, predictors of maximal LVOT gradient were basal septal thickness, bifid PM mobility, anterior mitral leaflet length, and abnormal chordal attachment to base of anterior mitral leaflet. Forty-five patients underwent surgery to relieve LVOT obstruction, of which 52% needed an additional nonmyectomy (MV repair/replacement or PM reorientation) approach. Conclusions— In hypertrophic cardiomyopathy patients without significant LV hypertrophy, in addition to basal septal thickness, anterior MV length, abnormal chordal attachment, and bifid PM mobility are associated with LVOT obstruction. In such patients, additional procedures on MV and PM (±myectomy) could be considered.